2009
DOI: 10.1136/jnnp.2008.171066
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcome of MCI subtypes and aetiologies in the Goteborg MCI study

Abstract: Objective The objective was to study the 2-year outcome of subjects diagnosed as having mild cognitive impairment (MCI). Methods Two hundred and nine subjects diagnosed as having MCI were examined with a comprehensive neuropsychological test battery and followed up after 2 years. Results After 2 years, 34 subjects (16%) were lost for follow-up. Those subjects did not differ significantly in terms of MCI subclassification, MMSE score or age and education. Of the 175 subjects followed up, eight (4.5%) had improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
90
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 43 publications
9
90
3
5
Order By: Relevance
“…These results might suggest that, contrary to the classical understanding of a-MCI as a risk factor for dementia, the a-sd-MCI subtype is in fact a "benign" form of MCI. This challenging idea was posed by Nordlund et al (2010) in an excellent investigation. The authors evaluated the 2-year outcome in a sample composed of a-sd-MCIs, a-md-MCIs, na-sdMCIs, and na-md-MCIs.…”
Section: Discussionmentioning
confidence: 99%
“…These results might suggest that, contrary to the classical understanding of a-MCI as a risk factor for dementia, the a-sd-MCI subtype is in fact a "benign" form of MCI. This challenging idea was posed by Nordlund et al (2010) in an excellent investigation. The authors evaluated the 2-year outcome in a sample composed of a-sd-MCIs, a-md-MCIs, na-sdMCIs, and na-md-MCIs.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, several longitudinal epidemiologic studies have found that transition from an MCI diagnosis back to normal cognition is fairly common. [2][3][4][5][6][7][8][9] Estimates of transition from MCI back to normal cognition have been quite varied, ranging from 4% to 15% [2][3][4][5] in clinic-based studies and 29% to 55% 6 -9 in population-based studies, depending in part on duration of follow-up. To date, few, if any, studies have focused on the subset of subjects who return to normal cognition after an MCI diagnosis.…”
mentioning
confidence: 99%
“…Тща-тельное изучение проблемы УКН позволяет утверждать, что большинство таких расстройств гетерогенны [8]; это определяется различными патогенетическими механизма-ми их развития, морфологическими проявлениями, осо-бенностями клинической картины и исходов [9][10][11]. Представление об УКН как о продромальной стадии БА было подтверждено исследованиями, которые показали, что когнитивная недостаточность может предшествовать и другим типам деменции, в частности СД, особенно связан-ной с патологией малых сосудов [12].…”
unclassified
“…Кро-ме основных вариантов, предлагается также выделять диз-регуляторный тип УКН, при этом подчеркивается его связь с цереброваскулярной патологией [14]. Ряд авторов указывает, что преобладающим в структуре УКН является вариант с множественным поражением когнитивных функций [11]. Каждый вариант обладает определенной за-кономерностью развития.…”
unclassified
See 1 more Smart Citation